Did subduction in the western Mediterranean drive Neogene alpine dynamics? Insights from analogue modeling - (:unkn) unknown (My University, 2024)
In the Western Alps, a first Late Cretaceous to Eocene “Pyrenean-Provençal” compressive phase accommodating N-S shortening resulting from the convergence between Africa and Eurasia is classically described. It is followed by the Neogene “Alpine phase” accommodating E-W shortening. Since this major tectonic change is not explained by a modification of the global Africa-Eurasia convergence, it should be explained instead by more local causes, possibly by the subduction of the Ligurian Ocean that initiated in the Oligocene beneath the European and Iberian plates. In this paper, we present analogue models simulating the Neogene evolution of this subduction zone, in order to understand how it impacted the regional tectonics. Although models do not include the lithospheric plate overriding the subduction zone, their surface deformations share many similarities with the Neogene tectonics of Western Europe and Iberia. We observe that the tectonic evolution is largely controlled by the roll-back of the slab, that occurred much faster than the Africa-Eurasia convergence. Models reproduce the opening of the Western Mediterranean Basins and the dispersion of the AlKaPeCa continental fragments (Alboran, Kabylian, Peloritan and Calabrian blocks). They also show that the subduction of the Ligurian Ocean favors the counterclockwise rotation of Adria. In more elaborated models, we introduced a pre-existing weakness along the Africa and Adria margins, to reproduce the break-off of the oceanic slab that followed the beginning of continental subduction both in Northern Africa and Adria. Slab break-off is followed by the exhumation of the subducted continent. We observe that the influence of subduction on the kinematics of Adria largely decreases following slab break-off. In the models, the total counterclockwise rotation of Adria varies between 7° and more than 30°, depending on the timing of slab break-off. Since the process of subduction modifies the displace
Keywords: African Research